Концепція комплексного лікування одонтогенних флегмон щелепно-лицевої локалізації - Варжапетян, Сурен Діасович; Копчак, А. В.; Varzhapetian, S. D.; Kopchak, A. V. (My University, 2023)
Актуальність. Одонтогенні флегмони щелепно-лицевої локалізації – поширена проблема сучасної медицини. За літературними даними встановлено, що одонтогенні флегмони щелепно-лицевої локалзації становлять від 2,7% до 3,4% усіх відвідувань лікаря-стоматолога. Мета роботи – проведення аналізу методів лікування одонтогенних флегмон щелепно-лицевої локалізації, обґрунтування факторів, що впливають на ефективність лікування гнійно-запальних захворювань. Матеріали і методи: проведено аналіз літературних джерел українських і зарубіжних авторів щодо перебігу, лікування й ускладнень щелепно-лицевої локалізації за останні 10 років. Результати дослідження та їх обговорення. Незважаючи на те, що лікування одонтогенних інфекцій покращилося за останні десятиліття, необхідне подальше вдосконалення цього питання. Основними факторами, які сприяли розвитку одонтогенних флегмон щелепно-лицевої локалізації, є незадовільна гігієна порожнини рота (76%), тютюнопаління (41%) і вживання алкоголю (19%). Odontogenic phlegmons of maxillofacial localization are a common problem of modern medicine. According to the literature data, it was established that odontogenic phlegmons of maxillofacial localization make up from 2.7% to 3.4% of all visits to the dentist. Unfortunately, these pathological processes do not have a tendency to decrease their prevalence among the population, which is due to the general low level of dental rehabilitation of patients, as well as reluctance to seek medical help and hope for the effectiveness of selftreatment. The aim of this work. The analysis of methods of treatment of odontogenic phlegmons of maxillofacial localization, substantiation of factors affecting the effectiveness of treatment of purulent-inflammatory diseases have been carried out. Materials and methods: The analysis of literary sources of Ukrainian and foreign authors regarding the course, treatment and complications of maxillofacial localization over the past 10 years has been conducted. Research results and their discussion. Although the treatment of odontogenic infections has been improved over the past decades, further improvements are needed in this area. The main factors that contributed to the development of odontogenic phlegmons of maxillofacial localization are unsatisfactory oral hygiene (76%), smoking (41%) and alcohol consumption (19%).
The concept of complex treatment of odontogeneous phlegmons of maxillofacial area
Keywords: флегмона; голова і шия; запальні процеси; phlegmon; head and neck; inflammatory processes